Acute Limb Ischemia and Pseudoaneurysm of Femoralis Artery Post Cardiac Catheterization in Pediatric - Perdana H. &; Kurnianingsih N. (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Acute Limb Ischemia and Pseudoaneurysm of Femoralis Artery Post CardiacCatheterization in Pediatric